Fatty Acid Composition, Fat Soluble Vitamins and Cholesterol Content of Farmed Rainbow Trout (Oncorhynchus mykiss) - Harlioglu, Ayse Gul (Zoological Soc Pakistan, 2012)
In this study, fatty acid composition, fat soluble vitamins (retinol, D-2, D-3, delta-tocopherol, alpha-tocopherol, K-1, K-2) and cholesterol content of farmed rainbow trout (Oncorhynchus mykiss) were investigated. The results show that there were significant differences in saturated fatty acids (SFAs) and polyunsaturated fatty acids (PUFAs) contents between trout muscle and diet (P<0.01 and P<0.05, respectively), and in SFA, PUFA, and monounsaturated fatty acids (MUFAs) contents between the trout liver and diet (P<0.05, P<0.001, P<0.001, respectively). However, no significant differences were found in the MUFAs between the muscle and diet. Docosahexaenoic acid (22:6 n-3, DHA) was the predominant fatty acid in the muscle and liver of trout. The ratio of n-3/n6 PUFA at 1.1 indicates the availability of n-3 PUFA that is beneficial for human health. Among the vitamins analyzed, vitamin E content was the highest in the muscle. It can be concluded that the farmed O. mykiss are good to human body containing rich PUFA (38.69 %) and vitamins (retinol, D-2, D-3, delta-tocopherol, alpha-tocopherol, K-1, K-2, 12.4, 1, 13,2, 58, 714, 626, 392 mu g/ 100 g, respectively) with low-level cholesterol (40.2 mg/100 g).
Keywords: Oncorhynchus mykiss; rainbow trout; fatty acid; cholesterol; fat-soluble vitamins; muscle; liver